Pengaruh Penerapan Media Gambar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi di SMA N 1 Abab Tahun Pelajaran 2018/2019 - Dwi Septia Sari; Yasir Arafat; Hendri Gunawan (Program Study of Accounting Education FKIP University of PGRI Palembang, 2019)
Based on the preliminary observations that researchers have done at Abab 1 Public High School, that learning media conducted using conventional learning methods using conventional learning methods has been going well but has not got maximum results, this can be seen from the 65% completeness and those who have completed 35% of the KKM 75 that had been determined by the school. The formulation of the problem in this study is